The Cambridge handbook of creativity - Kaufman, James C.; Sternberg, Robert J.; Cambridge Books Online (Online service). (Cambridge Cambridge University Press, 2010)
"The Cambridge Handbook of Creativity is a comprehensive scholarly handbook on creativity from the most respected psychologists, researchers, and educators. This handbook serves both as a thorough introduction to the field of creativity and as an invaluable reference and current source of important information. It covers such diverse topics as the brain, education, business, and world cultures. The first section, "Basic Concepts," is designed to introduce readers to both the history of and key concepts in the field of creativity. The next section, "Diverse Perspectives of Creativity," contains chapters on the many ways of approaching creativity. Several of these approaches, such as the functional, evolutionary, and neuroscientific approaches, have been invented or greatly reconceptualized in the last decade. The third section, "Contemporary Debates," highlights ongoing topics that still inspire discussion. Finally, the editors summarize and discuss important concepts from the book and look to what lies ahead" -- Provided by publisher
Part I. Basic Concepts: 1. Creativity research: a historical view Mark A. Runco and Robert S. Albert; 2. Theories of creativity Aaron Kozbelt, Ronald A. Beghetto, and Mark A. Runco; 3. Assessment of creativity Jonathan A. Plucker and Matthew C. Makel; 4. The roles of creativity in society Seana Moran; Part II. Diverse Perspectives on Creativity: 5. Cognition and creativity Thomas B. Ward and Yuliya Kolomyts; 6. The function of personality in creativity: the nature and nurture of the creative personality Gregory J. Feist; 7. How does a visual artist create an artwork? Paul J. Locher; 8. Organizational creativity: a systems approach Gerard J. Puccio and John F. Cabra; 9. Creativity in highly eminent individuals Dean Keith Simonton; 10. Everyday creativity: process and way of life - four key issues Ruth Richards; 11. The neurobiological foundation of creative cognition Allison B. Kaufman, Sergey A. Kornilov, Adam S. Bristol, Mei Tan, and Elena L. Grigorenko; 12. Developmental approaches to creativity Sandra W. Russ and Julie A. Fiorelli; 13. Educational creativity Jeffrey K. Smith and Lisa F. Smith; 14. Cross cultural perspectives on creativity Todd Lubart; 15. Evolutionary approaches to creativity Liane Gabora and Scott Barry Kaufman; 16. Functional creativity: "products" and the generation of effective novelty David Cropley and Arthur Cropley; Part III. Contemporary Debates: 17. Is creativity domain specific? John Baer; 18. The creativity-motivation connection Beth A. Hennessey; 19. Individual and group creativity R. Keith Sawyer; 20. Creativity and mental illness Paul J. Silvia and James C. Kaufman; 21. The relationship between creativity and intelligence Kyung Hee Kim, Bonnie Cramond, and Joyce VanTassel-Baska; 22. Divergent thinking, creativity, and ideation Mark A. Runco; 23. Creativity in the classroom Ronald A. Beghetto; Part IV. Conclusion: 24. Constraints on creativity: obvious and not so obvious Robert J. Sternberg and James C. Kaufman
Title from title screen (viewed on November 17, 2023)
Also issued in print format
Mode of access: World Wide Web
Keywords: Creative ability